Methanol Toxicity: Case Report - Yıldırım Can, Hümeyra; Kırbıyık, Halil (The Bulletin of Legal Medicine, 2017)
Methyl alcohol is an alcohol commonly used in the industry. It is also used in illegally produced drinks. Methyl alcohol poisoning is a clinical condition that causes vision loss, basal ganglion damage and metabolic acidosis with high risk of death. Bicarbonate supplementation, antidote administration and hemodialysis are applied to correct metabolic acidosis. We present in this study a 45-year-old male who was admitted to the Eye Polyclinic with sudden visual loss and was treated as methyl alcohol poisoning due to drinking 48 hours ago.